2009
DOI: 10.3844/ajessp.2009.94.98
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Response to the Application of Amendments in a Contaminated Soil with Trace Elements

Abstract: Problem Statement:The anthropogenic activities can cause adverse effects in soils, increasing in some situations trace elements contents, impacting negatively both the microbial biomass and activity. Among the practices used for the recovery of soil quality we can find the application of organic amendments or the product of their composting. These can adsorb trace elements decreasing their availability and increasing the soil microbial biomass. The microorganisms of the soil use to be considered as sensitive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For the soils under study, it was observed an increase in P sorption with temperature In addition, at high temperature a large proportion of P adsorbed permanently, thereby decreasing the equilibrium P concentration in soil solution Huang et al (2012). In addition temperature plays a significant role for the glucose concentrations (Soares et al, 2011) and in soil due to the presence of microbial activity may also alter (Branzini et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…For the soils under study, it was observed an increase in P sorption with temperature In addition, at high temperature a large proportion of P adsorbed permanently, thereby decreasing the equilibrium P concentration in soil solution Huang et al (2012). In addition temperature plays a significant role for the glucose concentrations (Soares et al, 2011) and in soil due to the presence of microbial activity may also alter (Branzini et al, 2014).…”
Section: Discussionmentioning
confidence: 96%